Development of a physical geometric phantom for deformable image registration credentialing of radiotherapy centers for a clinical trial. Issue 7 (22nd June 2021) - Kadoya, Noriyuki; Sakulsingharoj, Siwaporn; Kron, Tomas; Yao, Adam; Hardcastle, Nicholas; Bergman, Alanah; Okamoto, Hiroyuki; Mukumoto, Nobutaka; Nakajima, Yujiro; Jingu, Keiichi; Nakamura, Mitsuhiro
Abstract: Purpose: This study aimed to develop a physical geometric phantom for the deformable image registration (DIR) credentialing of radiotherapy centers for a clinical trial and tested the feasibility of the proposed phantom at multiple domestic and international institutions. Methods and materials: The phantom reproduced tumor shrinkage, rectum shape change, and body shrinkage using several physical phantoms with custom inserts. We tested the feasibility of the proposed phantom using 5 DIR patterns at 17 domestic and 2 international institutions (21 datasets). Eight institutions used the MIM software (MIM Software Inc, Cleveland, OH); seven used Velocity (Varian Medical Systems, Palo Alto, CA), and six used RayStation (RaySearch Laboratories, Stockholm, Sweden). The DIR accuracy was evaluated using the Dice similarity coefficient (DSC) and Hausdorff distance (HD). Results: The mean and one standard deviation (SD) values (range) of DSC were 0.909 ± 0.088 (0.434–0.984) and 0.909 ± 0.048 (0.726–0.972) for tumor and rectum proxies, respectively. The mean and one SD values (range) of the HD value were 5.02 ± 3.32 (1.53–20.35) and 5.79 ± 3.47 (1.22–21.48) (mm) for the tumor and rectum proxies, respectively. In three patterns evaluating the DIR accuracy within the entire phantom, 61.9% of the data had more than a DSC of 0.8 in both tumor and rectum proxies. In two patterns evaluating the DIR accuracy by focusing on tumor and rectum proxies, all data had more than a DSC of 0.8 in both tumor and rectum proxies. Conclusions: The wide range of DIR performance highlights the importance of optimizing the DIR process. Thus, the proposed method has considerable potential as an evaluation tool for DIR credentialing and quality assurance.